Family medicine Practice Management - Shalihin, Mohd Shaiful Ehsan; Said, Abdul Hadi (IIUM Press, 2022)
Practice Management in a clinic refers to managing day to day issues about primary care practice. Practically, it involves decisions, actions, and resource allocation to enable the provision of professional services to meet the objectives of the organisation at the clinic. It requires an understanding of the needs of health professionals, patients, non medical staff and the public. The process involves planning, finance, technology application, information and most importantly, dealing with people.